2015
DOI: 10.1002/celc.201500113
|View full text |Cite
|
Sign up to set email alerts
|

A Solvate Ionic Liquid as the Anolyte for Aqueous Rechargeable Li–O2 Batteries

Abstract: A reversible high‐areal‐capacity metallic lithium anode is pivotal to develop high specific‐energy‐density lithium‐metal‐based batteries. A novel solvate ionic liquid has been prepared by mixing tetraethylene glycol dimethyl ether (G4) and lithium bis(fluorosulfonyl)imide (LiFSI). Raman measurements revealed that the solvent was completely complexed by lithium cations to form a solvate ionic liquid (SIL) when the molar ratio of solvent to lithium cations was lower than 2. A symmetrical Li/LiFSI‐2G4/Li cell sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Kinetic models and physical arguments indicate that 2D growth should occur when the critical island size ( L crit ) is greater than the separation between 2D nuclei ( L s ). To fulfil this condition, enhancing the surface diffusivity of D and nucleation density (decreasing L s ) or reducing the magnitude of the Ehrlich–Schwoebel barrier ( E e–s ) by the surfactant (increasing L crit ) are promising methods, which can be realized by the addition of halogenated salts20 or enhancing the operating temperature24. Yang et al 25.…”
mentioning
confidence: 99%
“…Kinetic models and physical arguments indicate that 2D growth should occur when the critical island size ( L crit ) is greater than the separation between 2D nuclei ( L s ). To fulfil this condition, enhancing the surface diffusivity of D and nucleation density (decreasing L s ) or reducing the magnitude of the Ehrlich–Schwoebel barrier ( E e–s ) by the surfactant (increasing L crit ) are promising methods, which can be realized by the addition of halogenated salts20 or enhancing the operating temperature24. Yang et al 25.…”
mentioning
confidence: 99%
“…% DOL electrolyte was reported to supress lithium dendrite formation at room temperature and high current density. 17 A 200 μm lithium foil was used as the anode. The contact area of the lithium anode with the interlayer electrolyte was 1.13 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Imanishi and co-workers 19 also reported that a solvated ionic liquid of G4 and LiFSI shows excellent cycling performance for lithium deposition and stripping at 60°C. The Li/LiFSI-2G4/Li cell showed no dendrite formation at 6.0 mA cm ¹2 and 60°C for 2 h polarization of charge and discharge after 16 cycles, where the specific area capacity was 12 mAh cm ¹2 .…”
Section: ¹2mentioning
confidence: 96%
“…There has been several approaches to suppress lithium dendrite formation, such as improving the mechanical properties of the SEI by adjusting the electrolyte composition, [38][39][40] exploiting a self-healing electrostatic mechanism, 16 and using a solvent with a high content of lithium salt. [17][18][19] The structural rigidity of a SEI layer modified with additives cannot be sustained during extended deposition and stripping. The self-healing electrostatic mechanism is quite attractive, 16 where at low concentration, selected cations (such as cesium or rubidium ions) exhibit an effective reduction potential below the standard reduction potential of lithium.…”
Section: Lithium Dendrite Formation From Liquid Electrolytesmentioning
confidence: 99%
See 1 more Smart Citation